Comparison of Onlay versus Sublay Mesh Repair in Ventral Hernia : Our Experience in a Peripheral Hospital - Pervin, Mst Shahnaj; Md Nuruzzaman, Hasan Shahriar; Sultana, Eliza; Ahmad, Anis Uddin (Journal of Surgical Sciences, 2021)
Background: Mesh repair is the standard procedure of choice for the ventral hernia repair. The common techniques for this surgery are onlay and sublay repair. But the superior technique between the two is yet to be established objectives. Objectives: We conducted this study to compare the results of Onlay with Sublay mesh repair for the treatment of ventral hernia. Methods: This comparative study was conducted at the department of Surgery, Shaheed Tajuddin Ahmad Medical College Hospital, Gazipur from April 2018 to April 2019. 20 patients withclinically diagnosed ventral hernia were randomized into two groups. The patients in group A had onlay mesh repair while those of group B hadsublay mesh repair. Comparison between the two methods were made in terms of operative time, technical ease, early post operative events specially drain & complication, hospital stay, recurrence. Result: Twenty patients between 20 to 70 years of age among whom 6 are male and 14 are female with different types of ventral hernia including paraumbilical, umbilical, epigastric and incisional, except with defect more than 15 cm were studied. The sublay repair took significantly longer operative time (p = .023). Onlay repair group had more seroma formation, wound infection and recurrence, though not statistically significant. Patients who underwent sublay repair had early removal of drains (3.7 ± .823 days vs 6 ± .738 days) which was significant (p= .000). At the same time sublay repair group had significantly shorter hospital stay than the onlay group (4.5 ± 1.900 days vs 6 ± 1.354 days, p= .023). Conclusion: Sublay repair seems to be a better alternative than onlay repair of Ventral hernia. Randomised controlled trial with larger case numbers is needed to validate the result. Journal of Surgical Sciences (2020) Vol. 24 (2) : 61-65